Adverb Selection Effectiveness In English Application Letter For Trade Correspondence - Bayu Islam Assasaki; Sulhairi; admin, admin (Prevenire: Journal of Multidisciplinary Science, 2022)
In today's human existence, the corporate sector has evolved to a very high level. Because of the quick pace of growth, people now have access to a wide range of career opportunities. And a job application letter is one of the highly vital letters and has a very tight tie with the world of business. This letter is the first step in making a meeting between an organization that functions as a target and the candidate who works as a letter writer, which will lead to an agreement over an employment connection. Concerning the act of composing this letter, it undoubtedly involves the application of adverbs or the selection of adverbs whose application is impacted by the context of the circumstance.